Ancoratus - Epiphanius, Saint, Bishop of Constantia in Cyprus, approximately 310-403 (The fathers of the church. A new translation, 2014)
"Epiphanius of Cyprus was lead bishop of the island from 367 until his death in 403, and he was a contemporary of several of the great church fathers of the patristic era, including Athanasius, Basil, and Jerome. He is well known among modern scholars for his monumental heresiology, the Panarion, as well as for his involvement in several ecclesiastical and theological controversies. Before he began to write his magnum opus, however, he had already completed the Ancoratus, an important theological treatise, written in the form of a letter to Christians in southern Anatolia. The Ancoratus addressed numerous theological issues, particularly in response to the continuous disputes about the divinity of the Son, the developing arguments over the divinity of the Holy Spirit, and the early quarrels over the Incarnation of Christ. In addition, he included his thoughts on proper biblical exegesis, the problematic theology of Origen, and the relationship of the Christian faith with Hellenistic culture."--Publisher description